Soil moisture content and maize grain yield under conventional and conservation agriculture practices - results of short term field tests in liselo, Namibia - Kudumo, L. P.; Itanna, F.; Thierfelder, Christian L.; Kambatuku, J. (Academic Journals, 2023)
This article focuses on the results from trials developed to monitor the short-term effects of conventionally tilled systems versus CA on soil quality and crop productivity under conditions of the major cropping systems in central, north-central and north-eastern regions of Namibia. Conventional tillage (CT), Minimum tillage (MT), Minimum tillage, mulch (MT-M), Minimum tillage, rotation (MT-R) and Minimum tillage, mulch and rotation (MT-MR) were the primary treatments tested. Significant differences (p≤0.000) among the treatments were observed in the 0-60 cm soil profiles where MT-M plots had the highest soil moisture content (39.8 mm, Standard Error of Mean 0.2815) over the study period. A significant difference (p=0.0206) in grain yield was observed in the second season with CT plots yielding the highest grain yield (3852.3 kg ha-1, standard error of mean 240.35). Results suggest that CA has the potential to increase water conservation and contribute to reduction of the risk of crop failure. Climate change driven degradation under conventional tillage necessitate alternative sustainable tillage methods. Conservation tillage methods and conservation agricultural practices that minimize soil disturbance while maintaining soil cover need to be adopted more locally as viable alternatives to conventional tillage.